Kajian kecenderungan minat kerja sendiri di kalangan pelajar-pelajar Universiti Teknologi MARA, Kelantan / Nik Abdullah Zawawi Che Mat and Md. Sabri Mohamad - Che Mat, Nik Abdullah Zawawi; Mohamad, Md. Sabri (2006)
Entered the career era in the 21st century are not as easy as it was supposed. In addition, Malaysia was ravaged the economic crisis during 1997. The growth rate of Malaysia economics are low (6.0%), caused the work opportunity are limited. By that, High Education Institute (HEI) graduates must ascertain themselves qualified and met the current work market demand, especially in the industrial sector. Total of unemployment rate among HEI graduates increased to 4 7000 students in 2003. This situation caused polemics among of the community's expert against quality of student and quality of the course content taught in highest education level. This study was to see the tendency stage of self-employment among University Technology MARA, Kelantan students. UiTM apply the Entrepreneur subject in education with course code ETR 300 Entrepreneur. This study also aimed at seeing acceptance of the students towards the entrepreneur subject to be applied in their career world. This study was undertaken on Diploma level students. About 220 students who consisted the semester 01 and the semester 06 students were involved as the respondent in this study. The tendency level was measured with used accurate matter contain two parts, the Part 1: Personal Details and the Part 2: Career Accurate Matter. Total questions in part 2 are 50 questions using five Likert Scale namely Strongly Disagree, Disagree, Unsure, Agree, and Strongly Agree. Results of the study showed the stage of student's UiTM tendency towards the work personally was interested with total of students 56.4%. The tendency stage of the semester 01 and semester 06 students were 55.3% and 58.6%. This situation pointed out that UiTM students are interest to become an· entrepreneur exposure from UiTM increased their interest. However, there are several obstacles apart from the range of UiTM side to handle them after graduated.